2020
DOI: 10.2147/dmso.s231656
|View full text |Cite
|
Sign up to set email alerts
|

<p>Visceral Adiposity Index and Chronic Kidney Disease in a Non-Diabetic Population: A Cross-Sectional Study</p>

Abstract: To investigate the correlation between visceral obesity and pathogenesis of chronic kidney disease (CKD) among non-diabetic individuals, and to evaluate the potential of visceral adiposity index (VAI) as a predictor of CKD. Patients and Methods: From December 2017 to March 2018, 1877 non-diabetic participants (male n=699, female n=1208) in southern China were recruited for a cross-sectional survey. Males and females were divided into four groups according to gender-specific quartiles of VAI scores. A logistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 37 publications
(41 reference statements)
0
24
0
Order By: Relevance
“…CI reflects central obesity and has also been reported to be a good indicator of MetS status [ 63 ]. VAI is a surrogate of visceral fat accumulation, and it can also be used to assess central obesity [ 64 ]. LAP can be used to assess visceral fat and TG levels, and it has been shown to reflect the risk of MetS and cardiovascular disease [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…CI reflects central obesity and has also been reported to be a good indicator of MetS status [ 63 ]. VAI is a surrogate of visceral fat accumulation, and it can also be used to assess central obesity [ 64 ]. LAP can be used to assess visceral fat and TG levels, and it has been shown to reflect the risk of MetS and cardiovascular disease [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Visceral fat is usually considered to be more metabolically active than subcutaneous fat, and thereby a better predictor of cardiometabolic risk [ 11 ]. It is therefore reasonable to believe that individuals with more visceral abdominal obesity could also run a higher risk of developing CKD [ 27 ]. A recent study by Miyasato et al .…”
Section: Discussionmentioning
confidence: 99%
“…A validation study of the equipment used in the present study concluded that the validity and reliability was acceptable, and that the method could be of value both for clinical use and field studies [ 33 ]. However, others have questioned the precision of the bioelectrical impedance method, especially for individuals with body mass indices greater than 34 kg/m 2 [ 27 ]. These individuals often have a relatively high amount of extracellular water and total body water, which might result in an overestimation of fat-free mass and an underestimation of fat mass.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some previous studies showed that prevalence of CKD is significantly associated with both VAI and LAPI. 20,21 Excess fat can indirectly induce kidney damage by increasing the prevalence of atherosclerosis, hypertension, or type 2 diabetes. 22,23 Furthermore, excess fat can directly exacerbate kidney injury via the inflammatory response, which produces adipokines such as TNF-α and IL-6 leading to change in renal hemodynamics.…”
Section: <0001mentioning
confidence: 99%